Penerapan Digitalisasi Blockchain Pada Perguruan Tinggi Untuk Mendukung Smart University - Ageng Setiani Rafika; Giandari Maulani; Ferry Firmansyah (UNIVERSITAS RAHARJA, 2022)
Technological developments in the world are increasingly complex, this makes the world community need digitalization-based technology to increase productivity and reduce costs, inorder to provide more benefits for users. Included in education, a university needs to implement digitization in its organization. In order to create a university that is more efficient, effective, flexible, and secure, technology must be used. Today a faster growing technology is needed, and that technology is blockchain. Blockchain is a concept that can help accelerate the growth of digital-based education. This study discusses the definition of blockchain application in universities. As well as how universities and blockchain are used to build bigger concepts, with the aim of enabling more students to benefit from implementing blockchain. To improve the quality of research, researchers will use two methods, the first will focus on the effect of research on the quality of education and second on the effect of research on academic performance. The results of this evaluation will be concluded to improve the quality of education, both lecturers and students in the university area.